Ubiquitin signaling in immune responses - Hu, Hongbo; Sun, Shao-Cong (Cell research, 2016)
Ubiquitination has emerged as a crucial mechanism that regulates signal transduction in diverse biological pro- cesses, including different aspects of immune functions. Ubiquitination regulates pattern-recognition receptor sig- naling that mediates both innate immune responses and dendritic cell maturation required for initiation of adaptive immune responses. Ubiquitination also regulates the development, activation, and differentiation of T cells, thereby maintaining efficient adaptive immune responses to pathogens and immunological tolerance to self-tissues. Like phosphorylation, ubiquitination is a reversible reaction tightly controlled by the opposing actions of ubiquitin ligases and deubiquitinases. Deregulated ubiquitination events are associated with immunological disorders, including auto- immune and inflammatory diseases.